KARAKTERISTIK DAN DAYA TERIMA KEFIR SINBIOTIK TEPUNG GEMBILI MODIFIKASI FISIK - Kartika Kartika; Irma Kusumastuti (Jurnal Gizi dan Pangan Soedirman, 2022)
Synbiotic drinks are products that contain probiotics and prebiotics that can provide a healthy effect on the body. One type of prebiotic drink that is well known is kefir, and Dioscorea esculenta tuber is one of the food commodities which is known to have a high content of prebiotics such as inulin. This study aims to determine the effect of adding physical modification of Dioscorea esculenta flour to the physical, chemical, and microbiological properties of synbiotic kefir. The method used in this research is an experiment with descriptive data analysis. The results of this study indicate that the addition of physically modified Dioscorea esculenta flour can reduce the pH value and increase the titrated acid total (TAT) value and the number of lactic acid bacteria in kefir. The results of the organoleptic test showed that there was no significant difference in color, aroma, taste, and texture of synbiotic kefir with the addition of physically modified Dioscorea esculenta flour with concentrations of 0%, 2%, 4%, and 6%.